Respuesta :
You plug in -1 wherever you see x
So here is the work:
F(-1)= 2*2 +5(-1) -17
= 4 + -5 -17
= -18
Let me know if this helped!
So here is the work:
F(-1)= 2*2 +5(-1) -17
= 4 + -5 -17
= -18
Let me know if this helped!
Answer:
Step by Step Solution:
More Icon
Reformatting the input :
Changes made to your input should not affect the solution:
(1): "x2" was replaced by "x^2".
Rearrange:
Rearrange the equation by subtracting what is to the right of the equal sign from both sides of the equation :
f*(x)-(2*x^2+5*x-17)=0
STEP
1
:
Equation at the end of step 1
fx - ((2x2 + 5x) - 17) = 0
STEP
2
:
Equation at the end of step 2
fx - 2x2 - 5x + 17 = 0
STEP
3
:
Solving a Single Variable Equation
3.1 Solve fx-2x2-5x+17 = 0
In this type of equations, having more than one variable (unknown), you have to specify for which variable you want the equation solved.
Step-by-step explanation: